2014
DOI: 10.5194/amt-7-2987-2014
|View full text |Cite
|
Sign up to set email alerts
|

Validation of XCH<sub>4</sub> derived from SWIR spectra of GOSAT TANSO-FTS with aircraft measurement data

Abstract: Abstract. Column-averaged dry-air mole fractions of methane (XCH 4 ), retrieved from Greenhouse gases Observing SATellite (GOSAT) short-wavelength infrared (SWIR) spectra, were validated by using aircraft measurement data from the National Oceanic and Atmospheric Administration (NOAA), the US Department of Energy (DOE), the National Institute for Environmental Studies (NIES), the HIAPER Pole-to-Pole Observations (HIPPO) program, and the GOSAT validation aircraft observation campaign over Japan. In the calculat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 59 publications
(62 reference statements)
3
15
0
Order By: Relevance
“…Additionally, we take the mean difference between TCCON XCH 4 and aircraft-based XCH 4 into account when calculating the coefficients C 0 over land and ocean for XCH 4 . In a comparative analysis at four locations, Inoue et al (2014) showed that aircraft-based XCH 4 was 8.6 ppb smaller than TCCON XCH 4 on average. Consequently, in this study, we used the values for C 0 shown in Table 3b (i.e., 6.0 ppb over land and 0.2 ppb over ocean) for the correction of GOSAT XCH 4 when comparing GOSAT XCH 4 with TCCON XCH 4 .…”
Section: Correction and Validation Procedures Of Gosat Datamentioning
confidence: 96%
See 4 more Smart Citations
“…Additionally, we take the mean difference between TCCON XCH 4 and aircraft-based XCH 4 into account when calculating the coefficients C 0 over land and ocean for XCH 4 . In a comparative analysis at four locations, Inoue et al (2014) showed that aircraft-based XCH 4 was 8.6 ppb smaller than TCCON XCH 4 on average. Consequently, in this study, we used the values for C 0 shown in Table 3b (i.e., 6.0 ppb over land and 0.2 ppb over ocean) for the correction of GOSAT XCH 4 when comparing GOSAT XCH 4 with TCCON XCH 4 .…”
Section: Correction and Validation Procedures Of Gosat Datamentioning
confidence: 96%
“…To calculate aircraft-based XCO 2 and XCH 4 (as described in the next paragraph), we also used tower data from the Meteorological Research Institute (MRI) in Tsukuba (Inoue andMatsueda, 1996, 2001) and the NOAA ESRL/GMD tall tower network in Park Falls, WI and West Branch, IA . Details of the aircraft and tower measurements are described in Inoue et al (2013) and Inoue et al (2014), except for the JMA aircraft and groundbased measurements. The JMA aircraft measurements are conducted by utilizing the cargo aircraft C-130H of the Japan Ministry of Defense (MOD) to collect flask air samples once a month during a regular flight between the mainland of Japan and Minamitorishima, an island located nearly 2000 km southeast of Tokyo (Tsuboi et al, 2013).…”
Section: Aircraft-based Datamentioning
confidence: 99%
See 3 more Smart Citations